El Uso del Portafolio como Recurso para Evaluar la Docencia Universitaria - Arbesú García, María Isabel; Argumedo García, Gabriela (Revista Iberoamericana de Evaluación Educativa, 2016)
El propósito de este trabajo es reflexionar críticamente sobre la forma en que se ha desarrollado la evaluación de la docencia universitaria en México, con la finalidad de plantear una forma de evaluación docente complementaria a la que actualmente se lleva a cabo en la Universidad Autónoma Metropolitana (uam), en donde se prioriza la mejoría de la enseñanza y se articula a la evaluación con procesos de formación del profesorado. Este trabajo se integra de tres apartados que corresponden a la evaluación comprensiva, participativa y reflexiva, el segundo la aplicación del portafolio y el tercero algunos resultados preliminares. Palabras clave: Portafolio, docencia, nivel superior, evaluación, México. The objective of this work is to reflect critically on the form in which the evaluation of university teaching in Mexico has been developed, in order to propose a second form of teaching evaluation complementary to the one that at the moment it has been utilized at the Autonomous Metropolitan University (UAM), in which is prioritized the improvement of the teaching and articulates to the evaluation with processes of formation of the teaching staff. This work is integrated by three sections that correspond to the comprehensive, participating and reflective evaluation, the second to the application of the portfolio and the third to some preliminary results. Keywords: Portfolio, teaching, higher level, evaluation, México.